Evolutionary legacy of the extirpated red wolf clings to life in gulf‐coast canids. Issue 21 (20th October 2022) - Sacks, Benjamin N.
Abstract : Before Europeans colonized North America, a uniquely American wolf roamed the eastern forests of southern Canada to Florida and west to the Great Plains. Known today as "red wolf" ( Canis rufus ) in the south and "eastern wolf" ( Canis lycaon ) in the north, evidence suggests that these indigenous forest wolves shared a common evolutionary history until only a few centuries ago when they were extirpated from the intervening majority of their historical range. While the eastern wolf persists today primarily as a small population in Algonquin Provincial Park, Canada, the red wolf was ostensibly driven from its last stronghold in gulf‐coastal Louisiana and Texas by 1980. The last‐known red wolves were taken captive for propagation and reintroduction. Today, the red wolf exists as 250 descendants of 12 founders and are distributed among 42 captive breeding facilities and one reintroduced population in coastal North Carolina. As red and eastern wolves declined in the 20th century, coyotes expanded from the west into the eastern forests, replacing them. Along with human persecution, coyote hybridization has been blamed for the late 20th century demise of the red wolf. However, rather than helping to drive the red wolf to extinction, coyote hybridization may have instead helped to preserve it. In this issue of Molecular Ecology, vonHoldt and colleagues provide the most comprehensive description yet of the substantial quantity and distribution of red wolf ancestry sequestered in southeastern coyote populations. They find the highest frequency of red wolf genes in coyotes from the gulf‐coastal sites where the last known wild red wolves occurred, but also present evidence for a high prevalence of red wolf genes in coyotes throughout the southeastern expansion zone. Given the significant reduction in genetic diversity in extant red wolves owing to their late 20th century population bottleneck, this coyote‐sequestered reservoir of red wolf genes could prove an important resource for red wolf conservation.